PROBLEMATIKA WAKAF TUNAI? - Puji Nurmaya; Martina Ari Purnama; Muh. Rosid (Institut Teknologi Bisnis dan Kesehatan Bhakti Putra Bangsa Indonesia, 2023)
Cash waqf has the potential to empower the economic and social community. This is reinforced by regulations through the Waqf Law and MUI Fatwa, but in implementation there are still problems regarding fund mobilization, management, and expansion of the use of funds. This study aims to describe the various problems of waqf implementation in Indonesia. The research in this paper uses a normative or library approach. The results of the study show that the problematic implementation of waqf is not only from the perspective of the government, but also from the community and economic institutions. In addition, more concrete implementation is needed from the central government to regional governments. Keywords: Waqf, Cash Waqf, Community Empowerment ABSTRAK Wakaf tunai berpotensi dalam pemberdayaan ekonomi dan sosial masyarakat. Hal ini diperkuat dengan regulasi melalui UU Wakaf dan Fatwa MUI, namun dalam pelaksanaan masih terdapat persoalan tentang mobilisasi dana, manajemen pengelolaan, dan perluasan pemanfaatan dananya. Penelitian ini bertujuan mendeskripsikan berbagai problematika pelaksanaan wakaf di Indonesia. Penelitian dalam tulisan ini menggunakan pendekatan normatif atau kepustakaan. Hasil penelitian menunjukkan bahwa problematika pelaksanaan wakaf tidak hanya dari perspektif pemerintah, namun juga masyarakat dan lembaga ekonomi. Selain itu diperlukan implementasi yang lebih konkret mulai dari pemerintah pusat hingga pemerintah daerah.